1998
DOI: 10.1007/s004170050066
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of photoreceptor cells in ornithine-induced retinopathy

Abstract: An intravitreal injection of ornithine caused primary damage to the RPE, and subsequently some of the photoreceptor cells revealed apoptosis by TUNEL assay. These findings suggest the dysfunction of the RPE causes photoreceptor cell death according to the intrinsic program of an apoptotic mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
(20 reference statements)
3
9
0
Order By: Relevance
“…The pathological changes mentioned above were consistent with the functional research exhibiting that scotopic sensitivity decreased more than photopic sensitivity in cases with AMD [51]. Maeda and colleagues revealed the apoptosis of photoreceptors after RPE damage caused by intravitreal injection of ornithine in rats, indicating the important role of RPE cells in maintaining photoreceptor integrity [52]. In AMD patients, apoptotic photoreceptors and RPE cells (TUNEL positive) were observed as well.…”
Section: Affected Neuronssupporting
confidence: 79%
“…The pathological changes mentioned above were consistent with the functional research exhibiting that scotopic sensitivity decreased more than photopic sensitivity in cases with AMD [51]. Maeda and colleagues revealed the apoptosis of photoreceptors after RPE damage caused by intravitreal injection of ornithine in rats, indicating the important role of RPE cells in maintaining photoreceptor integrity [52]. In AMD patients, apoptotic photoreceptors and RPE cells (TUNEL positive) were observed as well.…”
Section: Affected Neuronssupporting
confidence: 79%
“…Dunaief also suggested the Fas/Fas ligand system may be involved in photoreceptor apoptosis in AMD (Dunaief et al, 2002). Maeda et al observed that the loss of photoreceptors was directly related to loss of RPE after intravitreal ornithine-induced degeneration, suggesting the importance of RPE in photoreceptor viability (Maeda et al, 1998). In geographic atrophy, Kim et al observed that photoreceptors loss was associated with RPE loss (Kim et al, 2002a).…”
Section: 0 Basic Definitions Of Exudative and Dry Age-related Maculmentioning
confidence: 99%
“…Although the pathogenesis of AMD remains unclear, there is evidence that degeneration or dysfunction of RPE cells often occurs in the early AMD pathogenesis and can be a predictor of photoreceptor loss although in cases such as outer retinal atrophy associated with pseudodrusen, photoreceptor loss can precede RPE disease. [91][92][93][94][95]…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%